THE EFFECT OF PROFITABILITY LIQUIDITY ON STOCK PRICES IN MINING SECTOR COMPANIES ON THE INDONESIA STOCK EXCHANGE IN THE PERIOD 2018-2021 - Putri Cindi Oktavia Tarihoran; Salman Faris (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The division of mining serves as a provider of energy resources, which are critical for economic growth and development in general. Companies may be encouraged to investigate listed resources because of the abundant potential of natural resources. In this study, 36 financial report samples and quantitative approaches were applied. With a sig value of 0.345 larger than 0.05 and a Tcount value of 0.345 smaller than Ttable 2.028, the results indicate that the liquidity and profitability variables have a somewhat positive effect on share prices. However, the profitability variable, with a sig value of 0.024 < 0.05 and a Tcount value of 2.365 > Ttable 2.028, shows a partial positive influence but is not significant.